Evaluation of infertility counselling in Germany - Thorn, Petra; Wischmann, Tewes; Mayer-Lewis, Birgit (Archives of gynecology and obstetrics, 2024)
This paper reports on the first evaluation of infertility counselling in Germany.
Gesehen am 14.03.2024
Early access, published online: 3 January 2024
Keywords: Beratung; Kinderwunsch